The corona of a surface bubble promotes electrochemical reactions - Vogel, Yan; Evans, Cameron; Belotti, Mattia; Xu, L.; Russell, I.C.; Yu, L.J.; Fung, A.K.K.; Hill, N.S.; Darwish, Nadim; Gonçales, V.R.; Coote, M.L.; Swaminathan Iyer, K.; et al. (NATURE RESEARCH, 2020)
The evolution of gaseous products is a feature common to several electrochemical processes, often resulting in bubbles adhering to the electrode’s surface. Adherent bubbles reduce the electrode active area, and are therefore generally treated as electrochemically inert entities. Here, we show that this general assumption does not hold for gas bubbles masking anodes operating in water. By means of imaging electrochemiluminescent systems, and by studying the anisotropy of polymer growth around bubbles, we demonstrate that gas cavities adhering to an electrode surface initiate the oxidation of water-soluble species more effectively than electrode areas free of bubbles. The corona of a bubble accumulates hydroxide anions, unbalanced by cations, a phenomenon which causes the oxidation of hydroxide ions to hydroxyl radicals to occur at potentials at least 0.7 V below redox tabled values. The downhill shift of the hydroxide oxidation at the corona of the bubble is likely to be a general mechanism involved in the initiation of heterogeneous electrochemical reactions in water, and could be harnessed in chemical synthesis.